Prissättning av telefonsamtal - Harald Lang; Stefan Lundgren (The Research Institute of Industrial Economics (IUI), 1990)
– The paper addresses the question whether current tariffs for telecommunications services provided by the Swedish telecommunications company, Televerket (TVT), are optimal, second-best 'Ramsey' prices. Focusing on two tariffs for telecommunications services those on subscription and calling time the paper estimates whether it is possible to increase consumers' surplus with current net revenue for TVT unchanged.
Keywords: A00; 330